Covalent immobilization of xylanase produced from Bacillus pumilus SV‐85S on electrospun polymethyl methacrylate nanofiber membrane. (14th March 2013) - Kumar, Pankaj; Gupta, Ashish; Dhakate, Sanjay R.; Mathur, Rakesh B.; Nagar, Sushil; Gupta, Vijay K.
Abstract Polymethyl methacrylate (PMMA) nanofiber membrane (NFM) was synthesized by an electrospinning technique. These membranes were utilized as a support for immobilization of xylanase enzyme to study its pH stability, thermal stability, and reusability. The morphology of aligned NFM was studied by optical microscopy and scanning electron microscopy. The PMMA NFM was functionalized with phenylenediamine and activated with glutaraldehyde to yield an aldehyde group on its surface for covalent immobilization of xylanase. The Fourier transform infrared analysis of the covalently immobilized xylanase confirmed that the enzyme was immobilized on PMMA NFM via amide linkages. The immobilization efficiency of covalently bound xylanase was found experimentally to be 90%. A forward shift in pH optima from 6.0–7.0 (soluble enzyme) to 7.0–9.0 (immobilized enzyme) was observed after xylanase immobilization. The pH and temperature stability of xylanase were enhanced upon its covalent immobilization. The immobilized enzyme was active on repeated use and retained ∼80% of its initial activity after 11 reaction cycles. The improved thermal and operational stability of the covalently immobilized enzyme on PMMA NFM might be advantageous for industrial applications.